AFRICAN TRADITIONAL WORLDVIEW: INDIGENOUS RESOURCE FOR RETHINKING GLOBAL FAITH AND ECOCULTIC SPIRITUALITY - Appiah-Kubi, Francis; Aabaa, Gregory (Asian Horizons, 2019)
Africa possesses certain bodies of organized wisdom informed by their indigenous worldview that serve as a pool of resources for theologizing and advancing their spirituality in relation to the natural environment. Such indigenous resources which serve to re-think African theology and spirituality are embedded in African’s ‘ecocentric’ values and practices. The African traditional worldview provides strong religious basis for eco-cultic spirituality that must not be obviated in tackling the menace of the current oikocide confronting humanity and the Church. This article demonstrates how African Traditional worldview, through its immense indigenous resources contributes to the catholic ecotheology. The paper argues that the African cultural resources and traditions are significant in eco-theology and contributing to the development of African theology. The first section of the paper articulates global faith as a justificatory framework which allows us to listen to the African voice in the universal dialogue concerning spirituality and the care of the environment. While the second section focuses on the cosmovision of indigenous resources for re-theologizing in Africa, the third section discusses African spirituality with emphasis on the eco-cultic practices theologically conducive to environmental or ecological sustainability. We conclude by articulating an evolving global catholic ecological spirituality through African conservation techniques as a formidable effort in tackling the global ecological crisis.